Effects of thermal processing on the nutritional and functional properties of defatted conophor nut (Tetracarpidium conophorum) flour and protein isolates. Issue 6 (27th August 2017) - Iyenagbe, David O.; Malomo, Sunday A.; Idowu, Atinuke O.; Badejo, Adebanjo A.; Fagbemi, Tayo N.
Abstract: Conophor nut ( Tetracarpidium conophorum ) was processed using different heat treatments to explore its full potential as food ingredients. The raw, boiled, and toasted nuts were defatted and the proteins isolated by alkaline solubilization and isoelectric precipitation. The variously processed nuts were analyzed for the proximate and amino acid compositions, and functional properties. The protein contents of the isolate ranges between 86.86 g/100g and 87.74 g/100 g, about 1.5‐fold higher than those of the defatted flour samples. The essential amino acids of the isolates ranged between 40.57%–41.55%. Glutamic acid, aspartic acid, and arginine were the most predominant amino acids, while methionine and lysine were the first and second limiting amino acids, respectively. The protein efficiency ratio, biological values as well as the functional properties of the proteins were improved with processing. These properties may enhance the potential use of conophor nut protein isolates as high‐quality protein ingredient in food systems. Abstract : Conophor nut is an oil‐rich seed which has great potential in food ingredient. Heat processing was found to improve the protein efficiency ratio, biological value, and functional properties of the protein. These properties will enhance its use in food system.